Morbidity and mortality patterns of preterm low birthweight neonates admitted to referral hospitals in the Amhara region of Ethiopia: retrospective follow-up study - Yalemtsehay Dagnaw Genie; Belete Fenta Kebede; Mulualem Silesh Zerihun; Desalew Tilahun Beyene (BMJ Open)
Objective This study aimed to assess the morbidity and mortality patterns of preterm neonates with low birth weight admitted in the Amhara region referral hospitals in Ethiopia.Design Hospital-based retrospective follow-up study.Setting Amhara region referral hospitals, Ethiopia.Participants A total of 291 preterm neonates low birth weight that were admitted to referral hospitals in the Amhara region between 1 January 2017 and 30 December 2018 were reviewed. Data were entered into Epi-data V.4.4.2.1 and exported to STATA V.14 for analysis, and variables with a p value of <0.05 at 95% confidence level in multivariable logistic regression model analysis were declared as statistically significant associated factors of mortality.Primary outcome Morbidity and mortality patterns in preterm low birthweight neonates.Results This study revealed that 37.8% (95% CI 32.4% to 43.5%) of preterm low birthweight neonates died. The most common morbidities found were 219 (75.26%) hypothermia, followed by 201 (69.07%), 145 (49.83%), 39 (13.4%) and 24 (8.25%) with sepsis, respiratory distress, jaundice and congenital anomalies, respectively. Sepsis (AOR: 2.0; 95% CI 1.03 to 3.89), respiratory distress (AOR: 4.6; 95% CI 2.51 to 8.40), hypoglycaemia (AOR 3.91; 95% CI 1.09 to 10.52), APGAR score at fifth minute <7 (AOR 0.39; 95% CI (0.18 to 0.82) and duration of hospital stay below mean (<9.82 days) (AOR 0.17; 95% CI 0.09 to 0.33) were associated with mortality.Conclusion The mortality rate of preterm low birthweight neonates was high, indicating that this is a public health issue. Hypothermia, sepsis, respiratory distress, jaundice and congenital anomalies were the common morbidities. Sepsis, respiratory distress, hypoglycaemia, Apgar score at fifth minute <7 and duration of hospital stay below the mean were independent factors of mortality. However, these need to be further investigated in future research and appropriately addressed using prospective follow-up.